2000
DOI: 10.1016/s0960-9822(00)00723-5
|View full text |Cite
|
Sign up to set email alerts
|

Slk19p is necessary to prevent separation of sister chromatids in meiosis I

Abstract: Our results suggest that Slk19p is essential at the centromere of meiotic chromosomes to prevent the premature separation of sister chromatids at meiosis I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
49
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 40 publications
10
49
0
Order By: Relevance
“…The phenotype resembled that observed in the dyad mutant of Arabidopsis in which the majority of female meiocytes divide singly to give a dyad followed by an arrest in further development of the female gametophyte (Siddiqi et al, 2000). Single division meiosis has also been described for the spo12, spo13 and slk19 mutants of yeast (Klapholz and Esposito, 1980;Zeng and Saunders, 2000;Kamieniecki et al, 2000).…”
Section: Discussionmentioning
confidence: 88%
“…The phenotype resembled that observed in the dyad mutant of Arabidopsis in which the majority of female meiocytes divide singly to give a dyad followed by an arrest in further development of the female gametophyte (Siddiqi et al, 2000). Single division meiosis has also been described for the spo12, spo13 and slk19 mutants of yeast (Klapholz and Esposito, 1980;Zeng and Saunders, 2000;Kamieniecki et al, 2000).…”
Section: Discussionmentioning
confidence: 88%
“…We tested the ability of these deleted versions of Slk19p to activate the FEAR network by taking advantage of the fact that FEAR mutants form only dyads after meiosis (Klapholz and Esposito 1980;Kamieniecki et al 2000;Zeng and Saunders 2000;Buonomo et al 2003;Marston et al 2003). We created diploid strains homozygous for each deletion allele and scored for the ability of the strain to form tetrads after meiosis.…”
Section: Resultsmentioning
confidence: 99%
“…meiosis I spindle but not so much as to permit the assembly of prereplicative complexes onto the DNA, which would result in a new S phase. It has been shown that exit from meiosis I requires only the FEAR pathway, since mutants in this pathway are impaired in meiosis I spindle disassembly, whereas MEN inactivation does not affect exit from the first meiotic division (Kamieniecki et al 2000;Buonomo et al 2003;Marston et al 2003;Kamieniecki et al 2005). Notably, even though chromosome segregation during meiosis I is not efficient in FEAR network mutants, they are able to progress through meiosis II and form two spores (dyads) instead of four (tetrads) (Sharon and Simchen 1990;Marston et al 2003).…”
Section: Discussionmentioning
confidence: 99%